Evaluation of the effect of cellular SMS reminders on consistency of antiretroviral therapy pharmacy pickups in HIV-infected adults in Botswana: a randomized controlled trial - Reid, Michael J. A. (Health Psychol Behav Med, 2017)
OBJECTIVE: Several studies have demonstrated that cellular phone short message service (SMS) improve antiretroviral adherence for people living with HIV in Africa, although less data are available to support using SMS reminders to improve timeliness of antiretroviral therapy (ART) pharmacy pick up. This study tested the efficacy of SMS reminders on timeliness of ART pharmacy pickups at an urban clinic in Gaborone, Botswana. DESIGN: A randomized-controlled trial evaluating the effect of SMS reminders on ART collection for patients with HIV on treatment. METHODS: One hundred and eight treatment-experienced adult patients were enrolled and randomly assigned to a control group or an intervention group. Participants in the intervention group received SMS reminders that were sent in advance of monthly ART refills that needed to be collected. The primary outcome was 100% timeliness of pharmacy ART pickups. Secondary outcomes included frequency of physician visits, CD4 cell counts and viral loads. RESULTS: Baseline characteristics in the intervention (n = 54) and control arms (n = 54) were similar. After six months, 85% of those receiving SMS reminders were 100% on time picking up monthly ART refills compared to 70% in the control group (p = 0.064). In secondary analysis, there were no significant changes in the CD4 counts and viral loads over the course of the study. CONCLUSIONS: Timeliness of ART pickup was not significantly improved by SMS reminders. Additionally, the intervention had no impact on immunologic or virologic outcomes in treatment-experienced patients.